Concurrent Hepatoblastoma and Wilms Tumor Leading to Diagnosis of Beckwith-Wiedemann Syndrome. Issue 4 (17th May 2023) - Wolfe, Danielle M.; Webster Carrion, Andrea; Masukhani, Mahesh M.; Oberg, Jennifer A.; Pavisic, Jovana; El-Ali, Alexander; Gupta, Mala; Weng, Katherine; Glasser, Chana L.
Abstract : Beckwith-Wiedemann syndrome (BWS) is an epigenetic overgrowth disorder and cancer predisposition syndrome caused by imprinting defects of chromosome 11p15.5-11p15.4. BWS should be considered in children with atypical presentations of embryonal tumors regardless of clinical phenotype. Risk of malignancy correlates with specific molecular subgroups of BWS making molecular subclassification important for appropriate cancer screening. We report the first case of concurrent embryonal tumors in a phenotypically normal child, leading to the diagnosis of BWS with paternal uniparental disomy and describe the molecular classification of BWS as it relates to malignancy risk, along with approach to management.